Chemical Constituents of the Femoral Gland Secretions of Male Tegu Lizards (Tupinambis merianae) (Family Teiidae) - Martín, José (2011)
In spite of the importance of chemical signals (pheromones) in the reproductive behav-iour of lizards, the chemical compounds secreted by their femoral glands, which may be used as sexual signals, are only known for a few lizard species. Based on mass spectra, obtained by GC-MS, we found 49 lipophilic compounds in femoral gland secretions of male tegu lizards (Tupinambis merianae) (fam. Teiidae), including a very high proportion of carboxylic acids and their esters ranging between n-C8 and n-C20 (mainly octadecanoic and 9,12-octadecadi-enoic acids), with much less proportions of steroids, tocopherol, aldehydes, and squalene. We discuss the potential function of these compounds in secretions, and compare the com-pounds found here with those documented for other lizard species.